Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/2053-1583/abc7f9
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition from Au–Te surface alloy towards tellurene-like monolayer

Abstract: Two-dimensional (2D) chalcogen-based layers have proven to be the next generation of materials for potential high-tech applications, and it is very important to control their properties at the nanoscale. Herein, we discuss the structural and electronic properties of Au(111) surface after being exposed to high temperature vapor deposition of Tellurium (Te) in ultrahigh vacuum. The scenarios entailing the formation of 2D AuTe2 metal dichalcogenide or rather Au–Te alloy monolayer (ML) or even Tellurene single lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Surface alloys can be fabricated with long-range order and high structural quality on noble metal (NM) surfaces by replacing surface atoms of the NM host materials with different kinds of metallic guest atoms. This allows the investigation of bonding mechanisms for otherwise immiscible metals and to design the spin-dependent band dispersion of surfaces states [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Surface alloys can be fabricated with long-range order and high structural quality on noble metal (NM) surfaces by replacing surface atoms of the NM host materials with different kinds of metallic guest atoms. This allows the investigation of bonding mechanisms for otherwise immiscible metals and to design the spin-dependent band dispersion of surfaces states [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are almost no reports on AuTe 2 chemical vapor deposition (CVD) growth on a large-scale. Recently, 2D Te growth on Au (111) substrates using molecular beam epitaxy has been reported, where the possible scenarios occurring between Te and Au, including the formation of compound AuTe 2 , toward the formation of monolayer tellurene on the Au substrate are discussed [25].…”
Section: Introductionmentioning
confidence: 99%
“…AgTe and AgSe display closed-packed atomic structures with a ( 3 × 3 ) structure. In addition, several metal monochalcogenide alloys show structures of chains, for example, Te on the Cu(111) system with ( 2 3 × 3 ) Cu–Te chains. Recent angle-resolved photoemission spectroscopy (ARPES) measurements have reported that CuSe and AgTe possess two-dimensional Dirac nodal line fermions (its Dirac point extends along the M – Γ – K high symmetry line, forming the Dirac nodal line), protected by the mirror reflection symmetry. ,, Moreover, chalcogen-based surface alloys are also promising substrates for epitaxial growth. For example, the CDW properties of TiSe 2 could be tuned by CuSe substrates .…”
Section: Introductionmentioning
confidence: 99%